Elimination of platelet factor 4 (PF4) from platelets reduces atherosclerosis in C57Bl/6 and apoE-/- mice - Sachais, Bruce S.; Turrentine, Tiffany; Dawicki McKenna, Jennine M.; Rux, Ann H.; Rader, Daniel; Kowalska, Anna M. (Thrombosis and Haemostasis, 2007)
Activated platelets, which release platelet factor 4 (PF4) are present in patients with atherosclerosis. To date, no direct invivo evidence exists for the involvement of PF4 in atherogenesis. In the current study, we tested the hypothesis that PF4 is atherogenic, and that genetic elimination of PF4 would protect mice from atherosclerosis. We have bred PF4-/- mice onto two athero-susceptible backgrounds, WT-C57Bl/6(WT) and apoE-/- to examine the importance of PF4 in atherogenesis. In order to induce atherosclerosis, WT and PF4-/- mice were fed an atherogenic diet for 30 weeks, while apoE-/- and apoE-/- PF4-/- mice were fed a high-fat Western-style diet for 10 weeks. Examination of lesions in the aortic roots of atherogenic diet fed mice demonstrated reduced atherosclerosis in PF4-/- (20% compared to WT). Examination of apoE-/- mice demonstrated similar changes, with apoE-/- PF4-/- mice demonstrating 37% of the aortic atherosclerotic burden compared to apoE-/- mice. Although we found similar levels of total and non-HDL cholesterol inWT and PF4-/- mice, HDL-cholesterol levels were increased in PF4-/- on both backgrounds. These data demonstrate, for the first time, that the platelet specific chemokine PF4 promotes atherosclerotic lesion development in vivo.
Keywords: Platelets; platelet factor 4 (PF4); chemokines; atherosclerosis